Pengaruh Celebrity Endorser Dan Brand Image Terhadap Keputusan Pembelian Produk Scarlett Whitening Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Negeri Makassar - Anggy Frischa Filatamara; Muh. Ikhwan Maulana Haeruddin; Ichwan Musa; Amiruddin Tawe; Muhammad Ilham Wardhana Haeruddin (Jurnal Manajemen Riset Inovasi, 2023)
This research aims to determine the influence of Celebrity Endorser and Brand Image on Purchase Decisions for Scarlett Whitening Products among Students at the Faculty of Economics and Business, Makassar State University. The sample used was 100 students from the Faculty of Economics and Business who had been selected based on predetermined criteria. Data collection techniques were carried out using questionnaires and literature studies. Data analysis techniques consist of validity tests, reliability tests, classic assumption tests consisting of normality tests, multicollinearity tests and heteroscedasticity tests, multiple linear analysis tests, hypothesis tests, determinant coefficient tests. The results of this research show that the Celebrity Endorser and Brand Image variables have a positive and significant influence on purchasing decisions. The variable that most dominantly influences purchasing decisions is the Celebrity Endorser variable and the one that has the least influence is the Brand Image variable. The dependent variable for purchasing decisions can be explained by the Celebrity Endorser variable and the remaining Brand Image is explained by other variables that were not examined in this research.